2000
DOI: 10.1177/096973300000700404
|View full text |Cite
|
Sign up to set email alerts
|

Patient Participation in Decision Making at the End of Life as Seen by a Close Relative

Abstract: The aim of the present study was to describe variations in patient participation in decisions about care planning during the final phase of life for a group of gravely ill patients, and how the different actors' manner of acting promotes or impedes patient participation. Thirty-seven qualitative research interviews were conducted with relatives of the patients. The patients' participation in the decisions could be categorized into four variations: self-determination, co-determination, delegation and nonpartici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Eight studies conducted in Australia, Canada, Sweden, the UK and the US added qualitative information on changes over time, mostly presented in case stories [40,52,53,66-70]. Different patterns emerged, which resonated with the quantitative findings.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Eight studies conducted in Australia, Canada, Sweden, the UK and the US added qualitative information on changes over time, mostly presented in case stories [40,52,53,66-70]. Different patterns emerged, which resonated with the quantitative findings.…”
Section: Resultsmentioning
confidence: 95%
“…In Morecambe Bay (UK), Thomas et al studied the preferences of 41 patients with advanced cancer and found they were strongly influenced by an assessment of caregivers’ capacity to care, irrespective of caregivers’ expressed desire to do it [52]. In Örebro (Sweden), Sahlberg-Blom et al interviewed bereaved relatives of 56 cancer patients and found that patient participation in end of life decisions, including on where to die, varied from self-determination and co-determination to delegation and non-participation, depending on context, patient’s personality, social network, cultural values and the extent to which their wishes and those of the caregivers could be supported [53]. …”
Section: Resultsmentioning
confidence: 99%
“…The ANs described, for example, how the older people would press their lips together, clearly showing that they did not want to eat. Sahlberg-Blom et al (23) have shown that autonomy at the end of life is not synonymous with self-determination in its purest meaning, but can take different forms. The attitudes of the nursing staff are likely to have a significant impact on the ongoing opportunities for older people to be autonomous on their own terms.…”
Section: Discussionmentioning
confidence: 99%
“…This can also create inadvertent selection bias that confounds generalizability of results (Ewing et al, 2004; Hudson et al, 2001). Self-determination is a core value of hospice and palliative care, and presumably support this in multiple ways, including patient education, providing informed choices regarding treatment options, actively involving family in decision-making to the extent desired by the patient, respecting ethnic and cultural traditions, and honoring the concept of holistic care (Sahlberg-Blom et al, 2000; Waldrop, 2006). For individuals at the end-of-life, promoting patient self-determination requires a climate in which decision-making is both facilitated and adaptive (i.e., accommodating to changes in attitudes based upon real-time experiences) at a time when control over various aspects of life is in decline.…”
Section: Threat To Patient Self-determinationmentioning
confidence: 99%